Enhancing SME Participation through Inventory Optimization and Barrier Assessment in Construction Supply Chains: Evidence from Surkhet Valley, Nepal - Bista, Bikash; Bhattarai, Subash Kumar; Kafle, Mukesh (Journal of Engineering Issues and Solutions, 2025)
This study aims to strengthen the participation of Small and Medium Enterprises (SMEs) in government-led construction supply chains by examining three key dimensions: material inventory optimization, identification of participation barriers, and actionable strategies for inclusion. The research was conducted in Surkhet Valley, Nepal, a region actively engaged in public infrastructure development. For the first objective, a three-year dataset of publicly procured construction materials was analyzed using ABC analysis based on usage value and frequency. Results revealed that five materials, including reinforcement and cement, accounted for 75% of total expenditure, highlighting the need for focused inventory control on high-value items. To address the second objective, perceptions from 58 SMEs were analyzed using Principal Component Analysis (PCA), identifying three major factors that explain 68.47% of the variance in SME challenges: (1) structural and operational barriers, such as bureaucratic delays; (2) financial and logistical constraints, like payment delays and demand volatility; and (3) capacity-related issues, including limited training and weak quality systems. For the third objective, the Relative Importance Index (RII) and Key Informant Interviews (KIIs) were used to prioritize remedial measures. Top-ranked strategies included cost minimization, simplified procurement paperwork, and improved logistics. KIIs further emphasized the importance of transparent payment systems and SME-friendly tender policies. The study concludes that a focused approach grounded in material classification, systemic barrier reduction, and SME-centric policy design can strengthen SME participation in public construction supply chains. Recommendations include ABC-based procurement planning, simplifying documentation requirements, SME training, and establishing preferential procurement policies.